A review of the geology and uranium, gold and iron ore deposits of the Pine Creek Orogen - Hollis, Julie; Wygralak, A. (International Union of Geological Sciences, 2012)
The Pine Creek Orogen comprises a succession of Paleoproterozoic sedimentary and volcanic rocks, unconformably overlying Neoarchean granitic basement and intruded by Paleoproterozoic mafic rocks and granites. The orogen is subdivided from west to east into the Litchfield Province, Central Domain and Nimbuwah Domain, based on the distinct timing and nature of sedimentation, magmatism and metamorphism. The orogen hosts a wide range of commodities, the most important of which are U and Au. Rifting of Neoarchean basement at 2020 Ma led to deposition of clastic, carbonate, and carbonaceous sedimentary and volcanic rocks in a shallow basin. At 1870 Ma, sedimentation in the Nimbuwah Domain was rapidly followed by burial, I-type granitic magmatism (1867-1860 Ma), compressional tectonism and mid-pressure amphibolite-facies metamorphism (1865-1855 Ma). Major U deposits occur in the Nimbuwah Domain within basal Paleoproterozoic strata, close to tectonised contacts with Neoarchean basement. Metamorphism of the Nimbuwah Domain coincided with sedimentation and volcanism in the Central Domain and Litchfield Province at 1863 Ma. This was followed by extensional high-temperature, low-pressure metamorphism (1855 Ma) and associated felsic and arc-related mafic magmatism (1862-1850 Ma) in the Litchfield Province. At or after this time, greenschist- facies metamorphism and upright folding and shearing occurred at upper crustal levels in the Central Domain, generating structural traps for subsequent Au- and Fe-bearing fluids. Almost all Au occurrences are associated with late to post orogenic, I-type Cullen Supersuite granites (1835-1820 Ma). Shortly thereafter, platform sediments were deposited in braided rivers across the orogen. The strong spatial heterogeneity in the distribution of U and Au suggests that the pre-existing crustal architecture of the orogen was a significant factor controlling their distribution.